The Phenomenological Methodology of Art: According to Dufrenne’s and Heidegger’s Thoughts - Shamsalmolok Mostafavi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
As the founder of phenomenology, Husserl himself did not use phenomenology to analyze art and works of art. Except for a few hints in Encyclopedia Britannica's article, he did not write anything in this area. However, he paved the way for the phenomenology of art and led many post-Husserlian phenomenologists to look at art from a phenomenological perspective. This article aims to show the application of the phenomenological method in aesthetics and analysis of works of art. To achieve this, we will first refer briefly to the ideas of M.Dufrenne (who is somewhat faithful to Husserl's intellectual tradition) to reveal to him how the phenomenology of aesthetic experience. Then according to Heidegger's views (which are further from Husserl's tradition), we will examine in the phenomenological analysis of art to see how Hermeneutic phenomenology can re-establish the neglected relationship between truth and art.